2014
DOI: 10.1016/j.lrr.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac anaplastic large cell lymphoma in an 8-year old boy

Abstract: We report on an 8 year old boy with primary cardiac anaplastic large cell lymphoma (ALCL), in whom the diagnosis was challenging and who was treated with modified chemotherapy without radiation therapy according to the ALCL 99 study protocol [1]. Two years and 4 months after completion of therapy the boy is in complete remission with normal cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Also cardiac ischemia resulting from lymphomatous deposits has been described . Sudden death may occur as a result of ventricular rupture, acute myocardial infarction, or ventricular arrythmias .…”
Section: Discussionmentioning
confidence: 99%
“…Also cardiac ischemia resulting from lymphomatous deposits has been described . Sudden death may occur as a result of ventricular rupture, acute myocardial infarction, or ventricular arrythmias .…”
Section: Discussionmentioning
confidence: 99%
“…We found a few case reports of cardiac involvement with ALCL, all of which occurred in patients between 8 and 29 years of age [15][16][17][18][19]. All these cases were ALCL ALK+, and only one report showed localized (= primary) cardiac lymphoma [15]. In all published cases, the cardiac involvement was identified based on clinical symptoms (syncopal episode, arrhythmia, heart failure).…”
Section: Discussionmentioning
confidence: 99%
“…We found some case reports on cardiac ALCLs in children or very young people in the literature [15][16][17][18][19]. We added the retrospective analysis of cardiac involvement in newly diagnosed lymphomas based on data from the Czech Lymphoma Study Group (CLSG) database, as most reported incidence of cardiac lymphoma was derived from the autopsies of patients with advanced disease or a set of cardiac tumors [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric ALCL with cardiac involvement at diagnosis is rare. Currently, only 2 cases are known to have been reported: an 8-year-old primary cardiac ALCL patient [ 9 ] and a 2-year-old ALCL patient with cardiac tamponade [ 10 ]. Pediatric ALCL with cardiac involvement, like pediatric ALCL in general, seems to respond favorably to steroids and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%